APPLYING PROVISIONS ON FORFEITURE OF PATRIMONIAL BENEFITS TO POLYGYNOUS CUSTOMARY MARRIAGES - Siyabonga Sibisi (Obiter, 2023)
The purpose of forfeiture-of-patrimonial provisions (forfeiture) is to ensure that a person does not benefit from the dissolution of a marriage that he or she has wrecked. Forfeiture provisions appear in section 9 of the Divorce Act 70 of 1979 (DA). They were initially designed only for civil marriages in a monogamous setting, and they were designed to apply to the three matrimonial property systems. Strictly speaking, customary marriages were neither in community of property nor out of community of property. Be that as it may, by reason of section 7 of the Recognition of Customary Marriages Act 120 of 1998 (RCMA), the three matrimonial property regimes apply to monogamous customary marriages. In addition, section 8 of the RCMA introduces section 9 of the DA to the dissolution of customary marriages. Monogamous customary marriages do not present a challenge to the application of section 9. It is polygynous customary marriages that present a complex situation. This article considers the application of forfeiture in polygynous customary marriages. It is concerned with a situation where a court orders forfeiture in divorce proceedings between a husband and one of his wives.